5-aminolevulinic acid enhances cell death under thermal stress in certain cancer cell lines. Issue 3 (4th March 2015) - Chibazakura, Taku; Toriyabe, Yui; Fujii, Hiroshi; Takahashi, Kiwamu; Kawakami, Mariko; Kuwamura, Haruna; Haga, Hazuki; Ogura, Shun-ichiro; Abe, Fuminori; Nakajima, Motowo; Yoshikawa, Hirofumi; Tanaka, Tohru
Abstract: 5-aminolevulinic acid (5-ALA) is contained in all organisms and a starting substrate for heme biosynthesis. Since administration of 5-ALA specifically leads cancer cells to accumulate protoporphyrin IX (PpIX), a potent photosensitizer, we tested if 5-ALA also serves as a thermosensitizer. 5-ALA enhanced heat-induced cell death of cancer cell lines such as HepG2, Caco-2, and Kato III, but not other cancer cell lines including U2-OS and normal cell lines including WI-38. Those 5-ALA-sensitive cancer cells, but neither U2-OS nor WI-38, accumulated intracellular PpIX and exhibited an increased reactive oxygen species (ROS) generation under thermal stress with 5-ALA treatment. In addition, blocking the PpIX-exporting transporter ABCG2 in U2-OS and WI-38 cells enhanced their cell death under thermal stress with 5-ALA. Finally, a ROS scavenger compromised the cell death enhancement by 5-ALA. These suggest that 5-ALA can sensitize certain cancer cells, but not normal cells, to thermal stress via accumulation of PpIX and increase of ROS generation. Graphical abstract: : 5-ALA treatment leads cancer cells to accumulate PpIX (heme precursor), resulting in ROS increase under thermal stress and thereby enhancing heat-induced cancer cell death.